Curriculum Development Innovation: Vocational High School Program Center of Excellence: Inovasi Pengembangan Kurikulum: Program Sekolah Menengah Kejuruan Pusat Keunggulan - Asngad, Toin; Doloh, Muhammadraais; Mahdi, Ali (Edukasi: Journal of Educational Research, 2023)
Developing an innovation-oriented curriculum in the modern era is a strategic step to improve the quality of education. This article examines the implementation of the Center of Excellence (PK) program at as an effort to create a generation that is competent and ready to compete in the job market. By integrating industry needs and implementing a project-based learning (PjBL) approach, this program offers innovation in vocational education. This research uses a qualitative descriptive approach with data collection methods through interviews, observation and documentation. Research findings show that the PK program at has succeeded in increasing the suitability of the curriculum to job market demands, student skills in the latest technology, as well as collaboration with the world of business and industry (DUDI). However, challenges such as teacher adaptation to technology and human resource management still need to be considered. By strengthening the capacity of educators and optimizing collaboration with partners, this program has the potential to become a model of innovation in vocational education that can be applied elsewhere